Survey of tick-borne zoonotic viruses in wild deer in Hokkaido, Japan - UCHIDA, Leo; HAYASAKA, Daisuke; TUN, Mya Myat NGWE; MORITA, Kouichi; MURAMATSU, Yasukazu; HAGIWARA, Katsuro (Journal of Veterinary Medical Science, 2018)
Tick-borne encephalitis (TBE) and severe fever with thrombocytopenia syndrome (SFTS) are both tick-borne zoonotic diseases caused by TBE virus (TBEV) and SFTS phlebovirus (SFTSV). In 2016, a second domestic TBE case was reported in Hokkaido, Japan, after an absence of 23 years. We conducted IgG ELISA for TBEV and SFTSV on 314 deer (Cervus nippon yesoensis) serum samples collected from 3 places in Hokkaido. There were 7 seropositive samples for TBEV but none for SFTSV by ELISA. The specificity of the 7 positive samples was confirmed by neutralization tests against TBEV, and 5 sera showed 320 to 640 of 50% focus reduction endpoint titers. Our results provide information about the infectious status of TBEV in wild deer in Hokkaido, Japan.